PENGARUH PENERAPAN GREEN ACCOUNTING DAN ENVIRONMENTAL PERFORMANCE TERHADAP FINANCIAL PERFORMANCE - Imansari, Lisa Cahyani; Miqdad, Muhammad; Wahyuni, Nining Ika (Jurnal Ilmiah Akuntansi Indonesia, 2024)
This research aims to examine the influence of green accounting and environmental performance on financial performance. The research subjects are companies in the basic chemical industry sector listed on the Indonesia Stock Exchange for the years 2021-2022, totaling 66 samples of companies selected through purposive sampling techniques. Data sources were obtained from annual reports and PROPER ratings. The results of the research indicate that green accounting does not have an impact on the financial performance of companies, whereas environmental performance has a positive effect on the financial performance of companies. The findings conclude that the environmental costs reported in the company's annual reports are not perceived as an enhancement to the company's image, aimed at providing a positive response to stakeholders. The success of companies in environmental performance, as indicated by the PROPER rating, is considered a sign of the company's commitment to conducting its operational activities while safeguarding the environment. This commitment is positively received by stakeholders.